2017
DOI: 10.4238/gmr16019101
|View full text |Cite
|
Sign up to set email alerts
|

GSTM1 polymorphism in patients with clinical manifestations of atherosclerosis

Abstract: ABSTRACT. Atherosclerosis is characterized by lesions, called atheroma or atheromatous plaques, in the inner layer of blood vessels, which block the vascular lumen and weaken the underlying tunica media. Several modifiable and non-modifiable risk factors for the development of atherosclerosis exist. The modifiable risk factors include hypertension, smoking, obesity, high LDL and low HDL cholesterol levels, sedentary lifestyle, and stress; the non-modifiable factors include diabetes mellitus, family history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
9
0
2
Order By: Relevance
“…A study in north India found no significant difference in any lipid phenotype between individuals with GSTM1 (-) and GSTM1 (+), but did find that the GSTM1 (-) genotype had a 2-fold increased risk of developing coronary artery disease in the cohort [60]. This gene has also been studied for association with atherosclerosis, and frequency of atherosclerosis in a GSTM1 polymorphic group were found to be 1.2 times higher than those in the control group in a study from a Brazilian cohort [61].…”
Section: Discussionmentioning
confidence: 99%
“…A study in north India found no significant difference in any lipid phenotype between individuals with GSTM1 (-) and GSTM1 (+), but did find that the GSTM1 (-) genotype had a 2-fold increased risk of developing coronary artery disease in the cohort [60]. This gene has also been studied for association with atherosclerosis, and frequency of atherosclerosis in a GSTM1 polymorphic group were found to be 1.2 times higher than those in the control group in a study from a Brazilian cohort [61].…”
Section: Discussionmentioning
confidence: 99%
“…Lower GSTM1 CG methylation content leads to the higher GSTM1 mRNA expression in T cells and knockdown of GSTM1 mRNA expression decreases T cells polarization to Th1 differentiation. GSTM1 genetic polymorphisms have been implicated in many diseases including atherosclerosis [ 37 ], and bladder cancer [ 38 ]. We are the first to show epigenetic control of the aging-dependent GSTM1 promoter methylation on suppression of the redox GSTM1 gene expression and lymphocyte T cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…They catalyze the reduced form of glutathione into xenobiotic substrates, turning such compounds more water-soluble in order to fulfill their function of detoxification [72]. GSTs polymorphisms are linked to innumerous diseases and anomalies such cancer [73], drug resistance [74], diabetes [75], atherosclerosis [39,40], and other inflammatory [76] and autoimmune diseases [77,78].…”
Section: Glutathione S-transferasementioning
confidence: 99%
“…GSTs from the mu and theta classes are particularly polymorphic. Null mutations in GSTM1 have been associated with a large variety of diseases and an increased susceptibility to toxins [39,73]. Null mutations in GSTM1 increases the susceptibility diseases as well [40,75].…”
Section: Glutathione S-transferasementioning
confidence: 99%
See 1 more Smart Citation